Cesarea Maritima : excavations at the promontory palace - University of Pennsylvania - Museum of Archaeology and Anthropology (2002)
[Dt.:] Kurzer Überblick über Aufbau und Ausgrabungen des Herodes-Palastes in der Provinzhauptstadt von Judäa, der dort in der Nähe des Theaters auf einer Halbinsel direkt an der heutigen Küstenlinie liegt. - [Engl.:] Short overview over structure and excavations of Herodes palace in the provincial capital of Judaea. The building is situated near the theater on a peninsula right beside the coastline of today.